Analisis Potensi Hazard Keselamatan Kerja pada Kelompok Mamalam di PT. Antam Tbk. UBPB Kalimantan Barat - Pradanti, Devy Dwi; Trisnawati, Elly; Alamsyah, Dedi; Budiastutik, Indah; Permata, Widya (Universitas Tanjungpura, 2026)
The agricultural sector is a major foundation of Indonesia's economy, employing 35.9 million people in 2022. However, this work has high risks that can lead to workplace accidents. This study aims to identify potential hazards and occupational safety risks faced by farmers. Using a descriptive quantitative cross-sectional approach, the study involved 52 farmers from the Mamalam Group of PT. Antam Tbk. UBPB West Kalimantan, from a total population of 211 workers. The research was conducted in June–July 2025. The results showed that throughout the work process, from land preparation to harvesting, farmers are exposed to various types of hazards: physical, ergonomic, chemical, biological, and psychosocial. Although some farmers have used Personal Protective Equipment (PPE), inconsistencies in its use remain. These findings indicate a need to improve the implementation of Occupational Safety and Health (OSH) procedures. Therefore, it is concluded that adherence to PPE use, attention to OSH signs, and increased awareness of potential hazards are crucial for minimizing the risk of workplace accidents. These efforts are essential for protecting workers from both physical and financial harm.